Music Culture from Interactive Methods Use in Their Lessons - Rustamjonova Dilkhavas Ravshvnbek qizi (Research Parks Publishing LLC, 2023)
In this article, pedagogy in secondary schools the methods of using technologies, the methods of using modern technologies to increase the effectiveness of lessons in music education, the types of interactive methods, and the ways of using methods and technologies to help schoolchildren to achieve both executive and creative competence took place.